Potential impact of COVID-19 on colorectal disease management - Campos,Fábio Guilherme (2020)
Abstract The current recommendations for management of colorectal diseases are still evolving, due to the limited experience on this issue. As the new coronavirus can be transmitted through breath droplets, by contact and orofecally, there is no consensus of how this fact may affect the investigation and treatment of anorectal diseases. Thus, high-quality multicenter studies are urgently needed to provide better information to both patients and the multiprofessional team, in order to build an effective pandemic response plan in our specialty. As a greater operative risk for infected patients has already been demonstrated, the next step lies on the identification of new therapeutic strategies that could minimize this effect on an individual basis. There is a present understanding that the COVID-19 pandemic should change some traditional practices. Therefore, the surgical treatment of suspected or known COVID-19 case demands specific insights. This article analyses potential influences regarding the treatment of patients with Colorectal Cancer (CRC) and Inflammatory Bowel Diseases (IBD). At present, elective surgery must be avoided, and the colorectal surgeon must carefully evaluate the risks and benefits of such decision. Within this context, a change toward nonsurgical and less aggressive modalities of CRC treatment may help to postpone definitive treatment. We also discuss the concerns regarding the viral infection among the population, the influence on clinical symptoms and the proposed modifications on therapeutic schemes.